"Build back better" approach to disaster recovery: Research trends since 2006. (May 2019) - Fernandez, Glenn; Ahmed, Iftekhar
Abstract: The "build back better" (BBB) approach to disaster recovery was first introduced in 2006 by the United Nations Secretary-General's Special Envoy for Tsunami Recovery, former US President William Clinton. In 2015, BBB became the second half of Priority 4 of the Sendai Framework for Disaster Risk Reduction 2015–2030, in recognition of its widespread use and adoption among disaster risk management practitioners, policy-makers, and researchers. This paper aims to summarize the significant advances related to BBB research in the past 13 years, and is expected to provide an overview of where the BBB concept and the related policy and practice are heading in the coming years. Themes identified from existing research include: the development of a BBB framework and of indicators; the spread of BBB research worldwide; practical examples of how to apply BBB principles; policies, legislation, and governance for supporting BBB; role of different stakeholders and actors; and capacity building for BBB. In theory, BBB is a desirable goal, but numerous experiences have proved that it is quite challenging to implement in practice. Additional research on BBB is needed to contribute to its successful implementation.